The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1631/jzus.b1100249
|View full text |Cite
|
Sign up to set email alerts
|

Elevated skin autofluorescence is strongly associated with foot ulcers in patients with diabetes: a cross-sectional, observational study of Chinese subjects

Abstract: Abstract:Objective: This study was designed to evaluate the association between skin autofluorescence (AF), an indicator of advanced glycation end-products (AGEs), and foot ulcers in subjects with diabetes. Methods: In this study, 195 Chinese diabetic subjects were examined. Their feet were examined regardless of whether an ulcer was present or not. Skin AF was measured with an AGE reader. Demographic characteristics and blood data were recorded. Results: The mean values of skin AF were 2.29±0.47 for subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 21 publications
8
58
0
Order By: Relevance
“…Despite this moderately high VPT value, the highest sAF quartile was independently associated with increased VPT. High sAF has already been reported in patients with foot ulcers, the main morbidity of DPN [27,28]. Our results show that even before reaching a VPT that reflects a severe lesion of a large nerve fibre or a high risk of foot ulcer, sAF reflects the worsening of large fibre function.…”
Section: Discussionsupporting
confidence: 67%
“…Despite this moderately high VPT value, the highest sAF quartile was independently associated with increased VPT. High sAF has already been reported in patients with foot ulcers, the main morbidity of DPN [27,28]. Our results show that even before reaching a VPT that reflects a severe lesion of a large nerve fibre or a high risk of foot ulcer, sAF reflects the worsening of large fibre function.…”
Section: Discussionsupporting
confidence: 67%
“…We provide reference SAF data for the first time in a Saudi population with potential application in a wide-range of translational and clinical studies. Skin autofluorescence assessment is not only important for cardiovascular risk assessment 13 21 22 and diabetes screening 14 , but has also been shown to have diagnostic value in renal failure 23 24 25 , retinopathy 26 27 , neuropathy 28 29 , foot ulceration 30 31 32 and schizophrenia 33 . We show a gender dependent association of SAF with age, SR value, diabetes, hypertension and obesity, discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies with the skin readers have shown that autofluorescence correlated strongly with the development of nephropathy [ 38 ] and neuropathy [ 39 ] including its association with the development of diabetic foot ulcers [ 40 ]. Conversely, its association with retinopathy was not nearly as strong.…”
Section: Discussionmentioning
confidence: 99%